Pengembangan Media Pembelajaran IPAS berbasis Lectora Inspire untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Negeri Kebondowo 01 Kabupaten Semarang - Alvina Verda Ardani; Desi Wulandari (Journal of Classroom Action Research, 2026)
This research is a Research and Development (R&D) development study with the ADDIE model which aims to develop, test the feasibility, and test the effectiveness of Lectora Inspire-based science learning media on the material "Forces Around Us". The research subjects included 6 students in a small-scale trial and 22 students in a large-scale trial, both from grade IV of Kebondowo 01 Elementary School, Semarang Regency. Data collection techniques used tests and non-tests. The test was in the form of a pretest-posttest, while the non-test included observation, interviews, questionnaires, and documentation. The results of product validation showed a percentage of feasibility from material experts of 90% and media experts of 95%, both categorized as very feasible. The results of the response questionnaire also supported the feasibility of the media, namely 98.3% in a small-scale trial, 95% in a large-scale trial, and 97.5% from teachers in the very feasible category. The effectiveness of the learning media was shown by the results of the N-Gain test of 80.38% (0.8038) which is included in the high category, as well as the results of the t-test with a Sig. value. < 0.001. These results indicate that the Lectora Inspire-based science learning media is feasible and effective in improving the learning outcomes of fourth-grade students at Kebondowo 01 Elementary School, Semarang Regency.